Hunting for leopards: Long-run country income dynamics in Africa - Jorge Saba Arbache; John Page (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper examines the country-level dynamics of long-run growth in Africa between 1975 and 2005. We are primarily interested in examining how growth has affected mobility and the distribution of income among countries. We analyse changes in the cross-country income structure and convergence. We also look for evidence of the formation of country groups or clubs. Finally, we use a novel method of breaking up the growth histories of African economies into medium term spells of growth accelerations and declines to see if a group of African leopards- the regional equivalent of Asia's tigers - is beginning to emerge.
Keywords: O11; O47; O55; O57; 330; GDP per capita; growth; Sub-Saharan Africa; Wirtschaftswachstum; Einkommensverteilung; Regionale Einkommensverteilung; Sozialprodukt; Afrika